A low cost wireless data acquisition system for distribution automation system - Ab Ghani, Mohd Ruddin; Raman, Siti Hajar; Wan Jusoh, Wan Nor Shela Ezwane; Mat Hanafiah, Mohd Ariff; Baharudin, Zikri Abadi (2013)
This paper presents the design and development of a 16F877A microcontroller-based wireless data acquisition system. Besides that, this paper also presents study of the possibility of different existing methodologies that linked to field data acquisition from distribution automation systems. Various existing data transmission technique was studied, especially for wireless systems such as satellite, radio, GSM and paging. The hardware and software implementation are described in this paper. The system will be used for reading, storing and analyzing data that obtained from DAS. The wireless communications are based on the GSM network. The laboratory results are compared with the simulation results to make the final conclusion of the algorithm function properly.